MASSIVE OPEN ONLINE COURSE IN MATHEMATICS: PERSPECTIVES ON COUNTRY, PUBLICATION TRENDS, RESEARCH APPROACHES, PARTICIPANTS, AND CONTENT ELEMENT - Sudirman, Sudirman; Rodríguez-Nieto, Camilo Andrés; Susandi, Ardi Dwi; Isnawan, Muhamad Galang; Pauzan, Muh (LPPM Universitas Jambi, 2025)
Massive Open Online Courses (MOOCs) have emerged as powerful tools that bridge vast learning resources with diverse global learners, particularly gaining prominence during and after the COVID-19 pandemic. While numerous studies have investigated the general application of MOOCs, limited research has specifically focused on their distribution and utilization within the field of mathematics education, especially in the post-pandemic context. This study aims to fill that gap by conducting a systematic literature review on MOOCs in mathematics, using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework to ensure a rigorous and replicable review process. At the identification stage, 2,349,886 articles were initially retrieved. After a comprehensive screening process based on inclusion and exclusion criteria, 78,191 articles were considered relevant. From this pool, 12 articles specifically addressed MOOCs in mathematics. However, only 6 articles met all the eligibility criteria for in-depth analysis. The findings reveal several key insights: (1) mathematics MOOCs are underrepresented in research, particularly in the context of school education; (2) research output on mathematics MOOCs has declined post-pandemic; (3) quantitative research methods dominate the field, limiting deeper qualitative insights; and (4) African countries remain significantly underrepresented in terms of both production and study of MOOCs in mathematics. This study contributes novel insights to the literature by highlighting geographic and methodological research gaps. It suggests that future research should explore mathematics MOOCs in school contexts, particularly using mixed-method approaches, and focus on understudied regions like Africa to promote equitable digital education access and innovation.